Learning Styles, Sense of Classroom Community and Student Engagement In Hybrid Learning - Saringatun Mudrikah; Anna Kania Widiatami (Edueksos: Jurnal Pendidikan Sosial & Ekonomi, 2023)
ABSTRACTThe aims of this study were: to analyze differences in learning outcomes, learning satisfaction, a sense of class community, and student involvement between the experimental and control classes, to analyze the effect of learning styles on learning outcomes, learning satisfaction, a sense of class community, and student involvement. This type of research is a quasi-experimental, with a population of accounting education students. The sampling technique uses purposive. Data collection techniques in the form of tests and questionnaires. Data analysis techniques in the form of prerequisite tests and hypothesis testing. The results of the study are: there is no difference in learning outcomes and learning satisfaction between hybrid and face-to-face learning, in hybrid learning there is a difference in sense of classroom community with face-to-face learning, in hybrid and face-to-face learning there is also no difference in student engagement, overall learning style. has a positive effect on learning outcomes, learning satisfaction, and sense of class community, and learning styles have no effect on student engagementKeywords: Learning styles, Sense of Classroom Community, Students'Â engagement, Hybrid learning